2007
DOI: 10.1002/sia.2566
|View full text |Cite
|
Sign up to set email alerts
|

Comparative characterisation by atomic force microscopy and ellipsometry of soft and solid thin films

Abstract: Ellipsometry and atomic force microscopy (AFM) were used to study the film thickness and the surface roughness of both 'soft' and solid thin films. 'Soft' polymer thin films of polystyrene and poly(styrene-ethylene/butylene-styrene) block copolymer were prepared by spin-coating onto planar silicon wafers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 49 publications
(65 reference statements)
3
22
0
Order By: Relevance
“…Another observation is that annealing exerted weak effect on film thickness. The tendencies found by ellipsometry and AFM correlated well in the case of CMCAB, corroborating with other reports in the literature for inorganic (Gesang et al 1995), enzymatic (Pancera et al 2006a, b) and polymeric (Mykhaylyk et al 2007) films. The ratio of angular coefficient obtained for acetone to that determined for ethyl acetate (Table 2) allowed estimating the experimental ratio D acetone /D EA as (1.4 ± 0.2), which evidenced that cellulose ester films prepared from acetone (D acetone ) solution were thicker (*40%) than those prepared from ethyl acetate (D EA ) solution.…”
Section: Resultssupporting
confidence: 92%
“…Another observation is that annealing exerted weak effect on film thickness. The tendencies found by ellipsometry and AFM correlated well in the case of CMCAB, corroborating with other reports in the literature for inorganic (Gesang et al 1995), enzymatic (Pancera et al 2006a, b) and polymeric (Mykhaylyk et al 2007) films. The ratio of angular coefficient obtained for acetone to that determined for ethyl acetate (Table 2) allowed estimating the experimental ratio D acetone /D EA as (1.4 ± 0.2), which evidenced that cellulose ester films prepared from acetone (D acetone ) solution were thicker (*40%) than those prepared from ethyl acetate (D EA ) solution.…”
Section: Resultssupporting
confidence: 92%
“…These values are compared very well with FFV % data obtained from the Bondi and van Krevlen method. It should be noted that the estimated values of FFV % are sensitive to the density of polymers . Thus, the reported FFV % values are higher for the PANI generated at temperature of 418 K as its density is lower (≈1.20 g cm −3 ) compared with the PANI obtained at 298 K (1.333 g cm −3 ).…”
Section: Resultsmentioning
confidence: 89%
“…Often, it was found that thin films had a very complicated structure, and the most appropriate way of simulating its dielectric functions was to treat the film as a mixture of two or more constituents 20. In conventional ellipsometry an effective medium approximation (EMA) was used to describe mixing of different media and to obtain quantitative information about the composition of a multicomponent film 21. In this surface structure, due to the intrusion of corrosion ions such as Cl − , H + , etc.…”
Section: Resultsmentioning
confidence: 99%
“…Spectroscopic ellipsometry (SE) is a nondestructive, sensitivity‐measuring tool, and does not require any sample preparation, which can sensitively monitor the gradual change of the surface films with sub‐nm‐order thickness and be used to obtain an accurate determination of surface film optical properties such as refractive index, extinction coefficient under/in ex situ conditions 12–14. By the ellipsometer, two parameters of ψ [arctan (relative amplitude ratio of p ‐ to s ‐polarized light)] and Δ (relative phase retardation between p ‐ and s ‐ polarized light), can simultaneously be sampled 15.…”
Section: Introductionmentioning
confidence: 99%